F-theory and AdS3/CFT2 - Couzens, Christopher; Lawrie, Craig (Journal of high energy physics, 2017)
We construct supersymmetric AdS3 solutions in F-theory, that is Type IIB supergravity with varying axio-dilaton, which are holographically dual to 2d N=(0,4)N=(0,4) \mathcal{N}=\left(0,4\right) superconformal field theories with small superconformal algebra. In F-theory these arise from D3-branes wrapped on curves in the base of an elliptically fibered Calabi-Yau threefold Y 3 and correspond to self-dual strings in the 6d N=(1,0)N=(1,0) \mathcal{N}=\left(1,0\right) theory obtained from F-theory on Y 3. The non-trivial fibration over the wrapped curves implies a varying coupling of the N=4N=4 \mathcal{N}=4 Super-Yang-Mills theory on the D3-branes. We compute the holographic central charges and show that these agree with the field theory and with the anomalies of self-dual strings in 6d. We complement our analysis with a discussion of the dual M-theory solutions and a comparison of the central charges.
Im Titel sind die Zahlen 3 und 2 tiefgestellt
Gesehen am 02.10.2018